2021
DOI: 10.3390/ma14020263
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Particles (VSOPs) Show Genotoxic Effects but No Functional Impact on Human Adipose Tissue-Derived Stromal Cells (ASCs)

Abstract: Adipose tissue-derived stromal cells (ASCs) represent a capable source for cell-based therapeutic approaches. For monitoring a cell-based application in vivo, magnetic resonance imaging (MRI) of cells labeled with iron oxide particles is a common method. It is the aim of the present study to analyze potential DNA damage, cytotoxicity and impairment of functional properties of human (h)ASCs after labeling with citrate-coated very small superparamagnetic iron oxide particles (VSOPs). Cytotoxic as well as genotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Notable steps were made in the synthesis of efficient magnetite/mesoporous media as drug delivery treatments, and in the near future, complex platform could be developed for cancer treatments [60,61,239]. Few nanomaterials have shown success in clinical cases, because supplementary research must be carried out in order to understand nanomaterial-human cell interactions and biological barriers in different types of cancers [240,241]. There are also industrial barriers because good laboratory practice has to be developed.…”
Section: Challenges and Discussion Regarding The Mnps Use In Cancer Therapymentioning
confidence: 99%
“…Notable steps were made in the synthesis of efficient magnetite/mesoporous media as drug delivery treatments, and in the near future, complex platform could be developed for cancer treatments [60,61,239]. Few nanomaterials have shown success in clinical cases, because supplementary research must be carried out in order to understand nanomaterial-human cell interactions and biological barriers in different types of cancers [240,241]. There are also industrial barriers because good laboratory practice has to be developed.…”
Section: Challenges and Discussion Regarding The Mnps Use In Cancer Therapymentioning
confidence: 99%
“…In Vitro Studies 2.1.1. Isolation and Culture of Human Adipose-Derived Stem Cells (hASCs) Human ASCs were isolated as described before [28,39,40] from the subcutaneous adipose tissue of healthy female donors (n = 4) after obtaining their informed consent. The study was approved by the Institutional Review Board of the Medical Department of the Julius-Maximilian University of Wuerzburg (grant #16/06, 25 July 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Although IONP’s toxicity is suggested, it also exhibits apparent genotoxic properties. The IONPs demonstrated that they directly intercalate with DNA, breaking DNA strands. , Additionally, the IONPs may interact with the proteins and enzymes necessary for ATP synthesis . These ions might obstruct ribosomal activities and stop them from synthesizing proteins.…”
Section: Antimicrobial Mechanisms Of Ionpsmentioning
confidence: 99%